Hypoxia inducible factor-1α promotes cell proliferation and migration in human pancreatic cancer cell line Patu8988 - Fan, Guang-Lei; Deng, Min-Bin; Peng, et al., Ming-Ya (European Journal of Oncology and Environmental Health, 2014)
Aim: Pancreatic cancer cells could survive and proliferate under severe hypoxia, with high expression of hypoxia inducible factor-1α (HIF-1α), which plays a crucial role in cell energy metabolisms, tumor angiogenesis and metastasis in cancer cells. This study investigates the role of HIF-1α on cell proliferation and migration of pancreatic cancer cells. Materials and methods: HIF-1α was knocked down in human pancreatic cancer cell line Patu8988 using siRNA. Cell proliferation was analyzed by MTT assay and cell cycle was analyzed by flow cytometry. Cancer cell mobility was assessed by a migration assay with Boyden chambers. Results: Cell proliferation analysis showed cells with decreased cell growth by MTT assay and G1/S phase cell cycle arrest using flow cytometry. Cancer cell mobility was significantly decreased when the HIF-1α was down-regulated, as assessed by a migration assay with Boyden chambers. Conclusion: These results suggested that down-regulation of HIF-1α could inhibit cell proliferation, and decreased tumor cell migration, which provided a new perspective in understanding the pleiotropic role of HIF-1α in pancreatic cancer.